Glassy carbon MEMS for novel origami-styled 3D integrated intracortical and epicortical neural probes. (4th April 2018) - Goshi, Noah; Castagnola, Elisa; Vomero, Maria; Gueli, Calogero; Cea, Claudia; Zucchini, Elena; Bjanes, David; Maggiolini, Emma; Moritz, Chet; Kassegne, Sam; Ricci, Davide; Fadiga, Luciano
Abstract: We report on a novel technology for microfabricating 3D origami-styled micro electro-mechanical systems (MEMS) structures with glassy carbon (GC) features and a supporting polymer substrate. GC MEMS devices that open to form 3D microstructures are microfabricated from GC patterns that are made through pyrolysis of polymer precursors on high-temperature resisting substrates like silicon or quartz and then transferring the patterned devices to a flexible substrate like polyimide followed by deposition of an insulation layer. The devices on flexible substrate are then folded into 3D form in an origami-fashion. These 3D MEMS devices have tunable mechanical properties that are achieved by selectively varying the thickness of the polymeric substrate and insulation layers at any desired location. This technology opens new possibilities by enabling microfabrication of a variety of 3D GC MEMS structures suited to applications ranging from biochemical sensing to implantable microelectrode arrays. As a demonstration of the technology, a neural signal recording microelectrode array platform that integrates both surface (cortical) and depth (intracortical) GC microelectrodes onto a single flexible thin-film device is introduced. When the device is unfurled, a pre-shaped shank of polyimide automatically comes off the substrate and forms the penetrating part of the device in a 3D fashion. With the advantage of being highly reproducible and batch-fabricated, the device introduced here allows for simultaneous recording of electrophysiological signals from both the brain surface (electrocorticography—ECoG) and depth (single neuron). Our device, therefore, has the potential to elucidate the roles of underlying neurons on the different components of µ ECoG signals. For in vivo validation of the design capabilities, the recording sites are coated with a poly(3, 4-ethylenedioxythiophene)—polystyrene sulfonate—carbon nanotube composite, to improve the electrical conductivity of the electrodes and consequently the quality of the recorded signals. Results show that both µ ECoG and intracortical arrays were able to acquire neural signals with high-sensitivity that increased with depth, thereby verifying the device functionality.